Nanomaterials in wound healing: From material sciences to wound healing applications. Issue 5 (16th September 2020) - Barroso, Andreia; Mestre, Henrique; Ascenso, Andreia; Simões, Sandra; Reis, Catarina
Abstract: An increasing number of innovative therapies have emerged in the field of wound healing. Nanostructured systems have been used to improve wound healing at different stages. The drug itself may be formulated at a nanoscale such that it can function as its own "carrier" or nanomaterials may be used as drug delivery vehicles. The present work covers the latest advancements on innovative nano‐based organic and inorganic materials. These novel drug delivery systems possess high stability, large surface area and tunable compositions and have demonstrated their wound‐healing properties using in vitro and in vivo models. Key areas in the development of new systems for wound care are the assessment of biological compatibility, the evaluation of anti‐microbial activity and the in vivo efficacy assessment using full‐thickness skin models. Due to the multifactorial nature of chronic wound occurrence robust models should support the investigation of new materials in order to elucidate mechanisms involved in the sequence of physiologic processes that take place at wound healing. Although several nanoparticles have been successfully tested both in vitro and in vivo, researchers are still investigating the approaches to implementing large scale production of nanotechnological platforms to wound healing treatments. Abstract : Several nanomaterials have been employed in wound healing in each type of healing phase (Hemostasis, Inflammation, Proliferation, Remodeling). The rationale for using each material strongly depends on the phase but also the duration of the therapeutic effect, dose, deepness and mechanism of action. NPs, nanoparticles.